Ultra-wideband polarization conversion metasurface and its application cases for antenna radiation enhancement and scattering suppression. Issue 1 (December 2017) - Zheng, Yuejun; Zhou, Yulong; Gao, Jun; Cao, Xiangyu; Yang, Huanhuan; Li, Sijia; Xu, Liming; Lan, Junxiang; Jidi, Liaori
Abstract A double-layer complementary metasurface (MS) with ultra-wideband polarization conversion is presented. Then, we propose two application cases by applying the polarization conversion structures to aperture coupling patch antenna (ACPA). Due to the existence of air-filled gap of ACPA, air substrate and dielectric substrate are used to construct the double-layer MS. The polarization conversion bandwidth is broadened toward low-frequency range. Subsequently, two application cases of antenna are proposed and investigated. The simultaneous improvement of radiation and scattering performance of antenna is normally considered as a contradiction. Gratifyingly, the contradiction is addressed in these two application cases. According to different mechanism of scattering suppression (i.e., polarization conversion and phase cancellation), the polarization conversion structures are utilized to construct uniform and orthogonal arrangement configurations. And then, the configurations are integrated into ACPA and two different kinds of metasurface-based (MS-based) ACPA are formed. Radiation properties of the two MS-based ACPAs are improved by optimizing the uniform and orthogonal arrangement configurations. The measured results suggest that ultra-wideband polarization conversion properties of the MS are achieved and radiation enhancement and scattering suppression of the two MS-based ACPAs are obtained. These results demonstrate that we provide novel approach to design high-performance polarization conversion MS and MS-based devices.